STUDI KARAKTERISTIK SUB DAERAH ALIRAN SUNGAI JETAK PADA DAERAH ALIRAN SUNGAI MELAWI KECAMATAN DEDAI KABUPATEN SINTANG - Boneta Angella; Riduansyah Riduansyah; Bambang Widiarso (Fakultas Pertanian Universitas Tanjungpura, 2022)
Jetak watersheds is already in a critical state and undergo changes caused by industrial waste, household. This research aimed to study the characteristics of the Jetak watershed. Jetak sub watershed has an area of 18734.27 hectares located in District Dedai Sintang. This study was conducted at two observation points that were on the downstream and upstream conducted on 6 consecutive days and subsequently analyzed in the laboratory TSS Land Quality and Health Faculty of Agriculture, University of Tanjungpura. The results showed that the pattern of Jetak’s river pipeline that was dendritic pattern and it shaped like a bird feather. IKD value was 0.0143 km / km2 and included the low category while the transverse profile of the river at the downstream and the upstream parabolic square shaped. Orde the river consisted of 2 ordes and water quality with an average pH value in the upstream was 6.01 and on the downstream was 6.46, the temperature on the upstream side had an average value was 27,90C and downstream has an average value was 27,70C, the brightness on the upstream side has an average value was 75.5 cm and the downstream section has an average value was 96.08 cm. Flow rate at the downstream has an average value was 7.418 m3 / sec and the upstream section was 0.790 m3 / sec. Discharge curve (r) of downstream was 0.084 and upstream was 0.746 with R2 downstream was 0,007 and the upstream was 0.557. The concentration of suspended sediment downstream had an average vaue was 9.5 mg / liter and upstream was 8.33 mg / liter. Downstream sediment discharge has an average was 6.13 tons / day and upstream was 0.57 tons / day. Arch sediment downstream (r) is 0.864 with R2 was 0.746 and on the upstream side (r) was 0.031 with R2 was 0.001.